Access 2007 for dummies - Ulrich-Fuller, Laurie 1961- (Wiley ;, 2007)
A beginner's guide to the latest version of the database management application explains the ins and outs of Access 2007, discussing the changes to the program's interface, as well as concepts including tables, relational database design, data integrity, formats, queries, wizards, forms, and new power user tools.
Includes index. - Print version record
Keywords: Microsoft Access. (Computer file); COMPUTERS; Programming Languages; SQL; Access